The Effectiveness of Effleurage and Trigger Point Techniques in Reducing Delayed Onset Muscle Soreness of the Quadriceps - Pratama, Naufal Yudi; Sumartiningsih, Sri (Universitas Negeri Semarang, 2024)
Abstract. Injuries resulting from physical activity can limit an individual’s mobility and performance. Appropriate therapeutic interventions are therefore required to minimize the risk and impact of injury. The present study aims to examine the effectiveness of a combination of effleurage and trigger point therapy in reducing pain caused by delayed onset muscle soreness (DOMS) among Muara Enim United athletes. The research employed a quasi-experimental design using a one-group pretest–posttest approach. A total sampling technique was applied, involving sixteen athletes as both the population and sample. The treatment was administered three times over the course of one week. Data were analyzed using the Wilcoxon test with the SPSS version 26 software. The independent variable was the combination of effleurage and trigger point therapy, while the dependent variable was the intensity of delayed onset muscle soreness. The results indicated a decrease in the mean pain score on the Visual Analogue Scale (VAS) to 3.8/10 after three treatment sessions. The findings demonstrate that the combination of effleurage and trigger point therapy effectively reduces pain intensity associated with DOMS when applied three times within one week. Abstrak. Cedera yang terjadi akibat aktivitas fisik dapat membatasi pergerakan dan performa seseorang. Oleh karena itu, diperlukan intervensi terapi yang tepat untuk meminimalkan risiko serta dampak cedera. Penelitian ini bertujuan untuk menguji efektivitas kombinasi teknik pijat effleurage dan trigger point therapy dalam menurunkan nyeri akibat delayed onset muscle soreness (DOMS) pada atlet Muara Enim United. Penelitian ini menggunakan desain quasi-eksperimen dengan rancangan one group pretest–posttest. Teknik pengambilan sampel menggunakan total sampling dengan jumlah populasi dan sampel sebanyak enam belas atlet. Perlakuan diberikan sebanyak tiga kali dalam jangka waktu satu minggu. Analisis data menggunakan uji Wilcoxon dengan bantuan program SPSS versi 26. Variabel bebas dalam penelitian ini adalah kombinasi teknik effleurage dan trigger point therapy, sedangkan variabel terikat adalah intensitas nyeri DOMS. Hasil penelitian menunjukkan penurunan nilai rata-rata nyeri pada Visual Analogue Scale (VAS) menjadi 3,8/10 setelah tiga kali perlakuan. Temuan ini membuktikan bahwa kombinasi pijat effleurage dan trigger point therapy efektif dalam menurunkan intensitas nyeri akibat DOMS dengan pemberian terapi sebanyak tiga kali dalam satu minggu.